Efforts of The People of Geyongan Village In Obtaining Rights To Former Pangonan Land - Junaedi Junaedi; Dandhy Nuralamsah Ramadhan; Aditiar Hafidh Anwar; Irma Maulida; Gusti Yosi Andri (Pelopor Publikasi Akademika, 2024)
The certificate of right to use on state land is a legal instrument that gives the holder the right to use state land for a certain period of time in accordance with the provisions of the applicable laws. This study examines the case of State Land intended for pangonan, which is located in Dukupace Block, Geyongan Village, Cirebon Regency, where the villagers use the abandoned Pangonan land, then they control it for various purposes such as agriculture and housing. Even though they have controlled the land for many years, the community does not have its ownership status. This will cause problems in the future if the status of the land is not yet owned by the people who occupy the land. The research method used is empirical juridical, with reference to various previous studies on state land ownership and land distribution justice. The results of the study show that there is a lack of public understanding of procedures and ownership conflicts. To overcome these obstacles, it is necessary to simplify the mechanism regarding rules and increase socialization. This study provides fair and inclusive policy recommendations, as well as concrete steps to improve the process of issuing use rights certificates and recognition of land rights based on long-standing physical tenure.